2018
DOI: 10.1002/ajim.22902
|View full text |Cite
|
Sign up to set email alerts
|

Knee pain in nursing home workers after implementation of a safe resident handling program

Abstract: The SRHP program did not eliminate knee physical loading, which should be reduced to prevent nursing home worker KP. Workplace psychosocial exposures (high job strain, low social support) also appeared germane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…The psychosocial determinants of physical activity in the workplace were analyzed in view of the associations found between psychosocial variables studied and physical activity. 2 , 32 Cross-sectional and longitudinal studies included in this review reported associations between physical activity and psychosocial factors affecting workers, including stress, psychosocial working conditions, 33 depression, 21 anxiety, 4 social capital, 34 work ability, 35 job satisfaction, 6 burnout, 14 and self-efficacy. 5 …”
Section: Discussionmentioning
confidence: 99%
“…The psychosocial determinants of physical activity in the workplace were analyzed in view of the associations found between psychosocial variables studied and physical activity. 2 , 32 Cross-sectional and longitudinal studies included in this review reported associations between physical activity and psychosocial factors affecting workers, including stress, psychosocial working conditions, 33 depression, 21 anxiety, 4 social capital, 34 work ability, 35 job satisfaction, 6 burnout, 14 and self-efficacy. 5 …”
Section: Discussionmentioning
confidence: 99%